Depressive symptoms and anti-N-methyl-D-aspartate-receptor GluN1 antibody seropositivity in the PROSpective cohort with incident stroke - Pia S. Sperber; Pimrapat Gebert; Leonie H.A. Broersen; Anna Kufner; Shufan Huo; Sophie K. Piper; Bianca Teegen; Peter U. Heuschmann; Harald Prüss; Matthias Endres; Thomas G. Liman; Bob Siegerink (Brain, Behavior, & Immunity - Health, 2023)
Background: Anti-NMDA-receptor GluN1 antibodies (NMDAR1-abs) are present in an autoimmune encephalitis with severe neuropsychiatric symptoms. We aimed to estimate the impact of serum NMDAR1-abs on depressive symptoms years after first-ever ischemic stroke (IS). Methods: Data were used from the PROSpective Cohort with Incident Stroke-Berlin (PROSCIS-B; NCT01363856). Serum NMDAR1-abs (IgM/IgA/IgG) were measured within 7 days after IS using cell-based assays. We defined seropositivity as titers ≥1:10, thereof low titers as ≤1:100 and high titers as >1:100. We used the Center for Epidemiological Studies–Depression (CES-D) scale to measure depressive symptoms at year one, two and three following IS. We calculated crude and confounder adjusted weighted generalized linear models to quantify the impact of NMDAR1-abs on CES-D assessed at three annual time-points. Results: NMDAR1-abs were measured in 583 PROSCIS-B IS patients (mean age = 67 [SD = 13]; 42%female; median NIHSS = 2 [IQR = 1–4]) of whom 76 (13%; IgM: n = 49/IgA: n = 43/IgG: n = 2) were seropositive, 55 (9%) with low and 21 (4%) with high titers. CES-D regarded over all follow-up time-points was higher in seropositive patients (βcrude = 2.56 [95%CI = −0.34 to 5.45]; βadjusted = 2.26 [95%CI = −0.68 to 5.20]) and effects were highest in patients with high titer (low titers: βcrude = 1.42 [95%CI = −1.79 to 4.62], βadjusted = 0.53 [95%CI = −2.47 to 3.54]; high titers: βcrude = 5.85 [95%CI = 0.20 to 11.50]; βadjusted = 7.20 [95%CI = 0.98 to 13.43]). Conclusion: Patients with serum NMDAR1-abs (predominantly IgM&IgA) suffer more severe depressive symptoms after mild-to-moderate IS compared to NMDAR1-abs seronegative patients.